2015
DOI: 10.1093/aje/kwu469
|View full text |Cite
|
Sign up to set email alerts
|

Propensity Score Methods for Analyzing Observational Data Like Randomized Experiments: Challenges and Solutions for Rare Outcomes and Exposures

Abstract: Randomized controlled trials are the "gold standard" for estimating the causal effects of treatments. However, it is often not feasible to conduct such a trial because of ethical concerns or budgetary constraints. We expand upon an approach to the analysis of observational data sets that mimics a sequence of randomized studies by implementing propensity score models within each trial to achieve covariate balance, using weighting and matching. The methods are illustrated using data from a safety study of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Matching methodology is a convenient way to adjust for preexisting differences between groups and therefore balances confounders and reduces bias. 23 It is also robust in determining outcomes of observational studies as it attempts to replicate a randomized experiment. 24 By creating 2 equivalent groups based on patient characteristics between younger and older women, the study minimizes bias due to the confounding adverse risk factors and allows for more meaningful conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Matching methodology is a convenient way to adjust for preexisting differences between groups and therefore balances confounders and reduces bias. 23 It is also robust in determining outcomes of observational studies as it attempts to replicate a randomized experiment. 24 By creating 2 equivalent groups based on patient characteristics between younger and older women, the study minimizes bias due to the confounding adverse risk factors and allows for more meaningful conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study design might understate the risk of sustained treatment with SGAs. 28 Although unlikely to explain the aggregate SGA effect, premorbid and unmeasured obesity might confound the analysis of differential risk for diabetes mellitus by specific SGA medications. Previous trials in smaller clinical samples suggested that newer SGAs (aripiprazole and ziprasidone) might carry fewer metabolic adverse effects, particularly weight gain, than other SGA medications.…”
Section: Discussionmentioning
confidence: 99%
“…26 This approach was previously applied to a reanalysis of the Women's Health Initiative. 27 Our methods appear in a separate report 28 and in eAppendix 1 in the Supplement. The institutional review board at The Children's Hospital of Philadelphia approved this study.…”
Section: Sample and Outcomesmentioning
confidence: 99%
“…Matching methodology has been reported to be a beneficial way to adjust for preexisting differences between racial groups, thus balancing confounders and reducing bias [21,22]. Matching can also be used as a means of endeavoring to replicate a randomized trial when attempting to determine outcomes in observational studies.…”
Section: Discussionmentioning
confidence: 99%